2014
DOI: 10.1155/2014/617343
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood-Flow with 99mTc-ECD Brain Perfusion SPECT in Landau-Kleffner Syndrome: Report of Two Cases

Abstract: Landau-Kleffner syndrome (LKS) is a rare childhood disorder characterized by acquired aphasia and epilepsy. 99mTc-ECD SPECT imaging was performed in two right-handed children with LKS. A relative decrease in perfusion was found in the left frontal-temporal cortices of both patients as well as in the left and right parietal cortices of one patient with aphasia, without clinical epilepsy. The degree of regional cerebral perfusion impairment did not correlate with the severity of the clinical and EEG abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Using 99mTc-ECD SPECT imaging, asymmetrical temporo-parietal perfusion seems to be a common finding in LKS [184]. Pullens et al, through the fMRI of a recovered adult LKS female, studied audiovisual multi-sensory processing, because LKS individuals are often skilled in reading, but fail in speech perception.…”
Section: Physiopathologymentioning
confidence: 99%
“…Using 99mTc-ECD SPECT imaging, asymmetrical temporo-parietal perfusion seems to be a common finding in LKS [184]. Pullens et al, through the fMRI of a recovered adult LKS female, studied audiovisual multi-sensory processing, because LKS individuals are often skilled in reading, but fail in speech perception.…”
Section: Physiopathologymentioning
confidence: 99%
“…MRI scans are normal in most LKS cases, but PET and SPECT studies have showed focal or multifocal changes or perfusion asymmetries predominantly affecting, but not restricted to the temporal regions [26]. Functional MRI study [27] suggested intact temporal lobe processing but an altered temporal to frontal connectivity.…”
Section: Lks and Etiologymentioning
confidence: 99%
“…The EEG is a basic component in LKS diagnosis, which typically shows abnormal epileptic discharges in children, while clinical seizures are observed in about 70% of the cases. EEG shows spike and wave discharges that are widespread, multifocal or shifting, mostly in the temporal region, sometimes unilateral and are particularly exacerbated Open Access Case during sleep [4].…”
Section: Introductionmentioning
confidence: 99%